Role of Climate-Smart Agriculture in Enhancing Farmers' Livelihoods and Sustainable Forest Management: A Case of Villages Around Songe-Bokwa Forest, Kilindi District, Tanzania - Nkumulwa, Hamza Omary; Pauline, Noah Makula (Frontiers in Sustainable Food Systems, 2021)
Climate change and variability are happening in Tanzania and its impacts are felt in the socio-economic sectors as have resulted in the decline of agricultural productivity and increased deforestation. Adoption of climate-smart agriculture (CSA) systems such as agroforestry, conservation agriculture, integrated nutrient management and agronomic techniques are very crucial for improving farmer’s livelihoods and reducing deforestation. However, little has been documented regarding the extent of actual measured reduced deforestation from implemented climate-smart agriculture practices and its impact on livelihoods. This study assessed the actual changes in deforestation levels and improved livelihoods caused by the adoption of climate-smart agriculture (CSA) practices. A simple random sampling technique was used to select 86 households for administering the semi-structured questionnaire, while purposive sampling was used to select the study area, 16 key informants and 32 members of four focus group discussions. Data was collected through semi structured household questionnaires, focus group discussions, key informants, GIS tools and observations. Quantitative data was analyzed using Arc GIS 10.3 software, SPSS version 16.0 and Excel Spreadsheet while Qualitative data analyzed through content analysis techniques. Findings show that farmers’ livelihoods have improved and also deforestation levels decreased as a result of increased adoption of CSA during in the past 30 years. Deforestation levels have been reduced from 64.6 ha per year during 1985-1995 to 11.8 ha per year during 1995-2005 and to 10.4 ha per year during 2005-2017. Further findings showed that agricultural area had been decreased from 4,534 ha in 1995 to 4039 ha in 2017 which is evidence that after the scale-up of CSA from the year 1992 agricultural practices were not contributing much to deforestation. Deforestation levels changed from 646 ha to 104 ha whileWhilst, increased crop production and income were observed, which in turn supported farmers in enhancing food security, purchasing production tools, livestock, payment for medical services, school fees and construction of modern houses. We found that adoption of climate-smart agriculture systems such as agroforestry, are very crucial for improving farmer’s livelihoods and reducing deforestation. Therefore, farmers need close mentoring on climate-resilient agroforestry systems. Therefore, farmers need close mentoring on climate-resilient agroforestry systems.